Study guides

☆☆

Q: What is 6n-3 equals 2n plus 9?

Write your answer...

Submit

Still have questions?

Related questions

9 - 5n

3 + 3n = 9 + 2n + 4n n = -2

6+5n=2n-9Isolate the variable by subtracting 2n and 6 from both sides.5n-2n=-9-63n=-15n=-5

2n-9=-4

18n + 27 or 9(2n + 3)

5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3

If 'n' is 8, then (2n - 7) is 9 .

Subract 5n from both sides and you get 9=-3n, then divide bother sides by -3 and you get n= -3

I'm assuming you are solving for n.2n + 6 = 7n - 9 {add nine to each side}2n + 15 = 7n { subtract 2n from each side}15 = 5n {divide each side by 5}3 = n

5n - 9 = 2n + 6 : Add 9 to both sides 5n = 2n + 15 : Subtract 2n from both sides 3n = 15 : Divide both sides by 3 n = 5

4n - 2n = 18 Therefore, 2n = 18 Therefore, n = 18/2 = 9

'n' can be any number, but when applied to (2n + 4), n = 2.5

2n-3 = 9 solve for n by first adding 3 to both sides 2n = 12 divided both sides by 2 n = 6

It is a linear Equation, the value of (n) here is 4.5 2n-3=6 2n=9 n=4.5

9 plus 87 equals 96.

12 plus 9 equals 21.

Subtract 2n from each side: 3n - 9 = 6 Add 9 to each side: 3n = 15 Divide both sides by 3: n = 5 Therefore, n = 5

3n + 9 = 3(n + 3)

If En = 2n then E9 = 2*9 = 18

If n = 9 then 2n must be 18.

-9 plus 6 equals -3.

-2n(n-9) = 0 n = 0 or n = 9

9-2n = 7

9+9+9+9 = 36

96